Problematizações a partir de situações emergentes do cotidiano : compreensões e possibilidades envolvendo relações quantitativas, medidas, formas e orientações espaço temporais em turmas de crianças de quatro anos - Cavalcante, Naila Fernanda Matielo (Universidade Federal de São Carlos, 2015)
This work aims to analyze four-year-old children’s speech in problematizations that were proposed by a teacher based in emerging situations present in the daily life of early childhood education. Here, the speeches that indicate the mathematical notions are prioritized. The questions that guided this research are listed as follows: Firstly, what mathematical notions can be displayed by four-year old-children in emerging situations that are part of the daily life of early childhood education? How can these emerging situations experienced during early childhood education enhance teacher’s work in terms of planning problematizations for fouryear- old children? The methodology is based on a qualitative perspective, specifically on research that the teacher herself does as a researcher. The data analysis is based on an interpretive vison of the children's manifestations expressed in a game context. In the analysis, the children's dialogues are contemplated as the problematizations are performed, and they are transcribed from video records. The research shows that the speeches, sensations, and children's questions in their daily routine at Municipal Center of Childhood Education reveals that when mathematical notions are considered by the teacher when planning problematizations that have the composition of a game, they can provide the presentation and the construction of mathematical language. These speeches and questions brought by children are related to emerging everyday situations, and are understood as to trigger learning situations. This perspective considers playing as the child's main activity and recognizes it as an active and historical subject who is immersed in a world full of mathematical notions since its birth. The problematization’s starting point, emerged from everyday situations, has proven to be a methodology that allows children to solve problem situations and to give them a breeding ground for developing mathematical notions in childhood education, respecting the needs and reasons for their learning. The children's speeches are permeated of problematizations about quantitative relations, measurements, shapes, and temporal space guidelines. Thus, when problematizing emerging everyday situations, the teacher considers latent apprenticeships, giving movement to the curriculum.
Keywords: Situações emergentes do cotidiano; Fala; Mediação; Noções matemáticas; Educação Infantil; Emerging everyday situations; Speech; Mediation; Mathematical Notions; Early Childhood Education; CIENCIAS HUMANAS::EDUCACAO